Intrabony Periodontal Defects Using Guided Tissue Regeneration (GTR): A Literature Review - Suci Pratiwi Suharto; Asdar Gani (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction : Guided tissue regeneration (GTR) has many used for periodontal regeneration in damage intrabony and has been the accepted treatment modality for almost 30 years. Many clinical studies have demonstrated that GTR is a successful modality of treatment for periodontal reconstructive surgery and has become the accepted procedure in most periodontal practices. This GTR has undergone a number of changes, including the use of several different membrane barrier materials for the stability of the space under the GTR membrane. Objective: This article aims to discussed periodontal treatment of intrabony defects using GTR. Literature Review: Periodontal regeneration can be defined as the complete restoration of lost periodontal tissue to its original texture and function. The procedure used to regenerate bone defects around teeth is known as guided tissue regeneration (GTR). Discussion: Treatment with GTR has been shown to be effective in preventing epithelial and gingival connective tissue cells from migrating to the root surface. The main results in the treatment of intrabony defects achieved by guided tissue regeneration are increased functional tooth support (clinical attachment and bone level), reduced pocket depth, and minimal gingival recession. Conclusion: From this literature review it was concluded that periodontal treatment of intrabony defects using GTR provides clinical results in the form of a good and significant increase in PD and CAL.